Improving students achievement on keeping the Integrity of the republic lesson (nkri) through role Play method with cooperative learning at the fifth Grade students in elementary school no. 25 bukit Kecil kecamatan iv jurai - Husni Husni (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Citizenship Education (Civics) is given from elementary school to senior high school. With Civics one will have the ability to know and understand the character and culture of the nation and make citizens who are ready to compete in the international world without leaving Teak self nation. Through Civics every citizen can observe themselves with the development of information and communication technology today that gives positive and negative impacts. Civics is also useful to equip learners inorder to have the ability to manage and utilize information to survive in an ever-changing, uncertain and competitive state. The research objectives are: Improving the mastery of the concept of decision-making relationship together by using props in the form of pictures and objects - objects around. Looking for information on student activeness in learning Civics about the Unitary State of the Republic of Indonesia. Describe the application method of playing a role in mod el cooperative leraning to improve learning outcomes joint decision fifth grade students of SD 25 State Small Hill District IV Jurai. In qualitative data collection activities, observers use teacher observation sheets. Observer gives a check mark (√) on the appearance column according to the indicator. The observations made by the observer (observer) is about the effectiveness of the method of playing a role in improving student motivation in learning civics in particular about the material p okok the Unitary Republic of Indonesia. To get more precise data, the focus of observation is emphasized on: Teacher activity in applying role play method, Child activity in learning implementation, Student activity in role play, Indicator observed on teacher observation sheet attached. Quantitative data obtained from the results of formative test values. From these results can be to measure the success rate of learning. From the results of formative test score can be known the success rate of the use of role playing methods in improving student motivation. The quantitative data is made in accordance with the assessment guidelines that have been made by the teacher. After the teacher gives an assessment and then analyze the grain matter The results of the study civics learning corrective action with the subject matter of the Unitary Republic of Indonesia in the first half of class V SD 25 State Small Hill District IV Jurai through cooperative learning model of learning through role-play method by effecting culture and globe props deemed sufficient. It is proven that there is an increase of learning resultor evaluation result of mean value above KKM is 90 and 96% completeness level